Evolution from electrophysiologic to hemodynamic monitoring: the story of left atrial and pulmonary artery pressure monitors - Mooney, Deirdre M.; Fung, Erik; Doshi, Rahul N.; Shavelle, David M. (Frontiers in Physiology, 2015)
Heart failure (HF) is a costly, challenging and highly prevalent medical condition. Hospitalization for acute decompensation is associated with high morbidity and mortality. Despite application of evidence-based medical therapies and technologies, HF remains a formidable challenge for virtually all healthcare systems. Repeat hospitalizations for acute decompensated HF (ADHF) can have major financial impact on institutions and resources. Early and accurate identification of impending ADHF is of paramount importance yet there is limited high quality evidence or infrastructure to guide management in the outpatient setting. Historically, ADHF was identified by physical exam findings or invasive hemodynamic monitoring during a hospital admission; however, advances in medical microelectronics and the advent of device-based diagnostics have enabled long-term ambulatory monitoring of HF patients in the outpatient setting. These monitors have evolved from piggybacking on cardiac implantable electrophysiologic devices to standalone implantable hemodynamic monitors that transduce left atrial or pulmonary artery pressures as surrogate measures of left ventricular filling pressure. As technology evolves, devices will likely continue to miniaturize while their capabilities grow. An important, persistent challenge that remains is developing systems to translate the large volumes of real-time data, particularly data trends, into actionable information that leads to appropriate, safe and timely interventions without overwhelming outpatient cardiology and general medical practices. Future directions for implantable hemodynamic monitors beyond their utility in heart failure may include management of other major chronic diseases such as pulmonary hypertension, end stage renal disease and portal hypertension.